2010
DOI: 10.1177/1088868310371101
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Self-Aspects Framework: Self-Concept Representation and Its Implications

Abstract: The multiple self-aspects framework (MSF) conceives of the self-concept as a collection of multiple, context-dependent selves. From this perspective, five principles are derived, addressing issues such as how context activates particular regions of self-knowledge and how self-relevant feedback affects self-evaluations and affect. Support for these principles is discussed. Furthermore, the MSF advances several novel predictions, including how active self-aspects filter one's experiences and perceptions, how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
350
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(374 citation statements)
references
References 178 publications
(240 reference statements)
18
350
1
5
Order By: Relevance
“…Seema reported that "I tried to treat my students like adults but honestly, it is still very much like secondary school… teaching has to be like what it was in school". Seema clinging on to her professional teacher identity reflects how selfpreservation (Sedikides, Gaertner, & O'Mara, 2011) makes new and contrasting self-concepts less easily assimilated (McConnell, 2011). This desire to continue to focus on maintaining a credible role as a teacher is understandable.…”
Section: The Development Of Uet's Academic Identitiesmentioning
confidence: 99%
“…Seema reported that "I tried to treat my students like adults but honestly, it is still very much like secondary school… teaching has to be like what it was in school". Seema clinging on to her professional teacher identity reflects how selfpreservation (Sedikides, Gaertner, & O'Mara, 2011) makes new and contrasting self-concepts less easily assimilated (McConnell, 2011). This desire to continue to focus on maintaining a credible role as a teacher is understandable.…”
Section: The Development Of Uet's Academic Identitiesmentioning
confidence: 99%
“…Taking into account that various factors influence the selfconcept, consumer researchers have also emphasized the importance of interdisciplinary research that uses multiple theoretical lenses to study consumer phenomena based on the self (McConnell 2011;Pham 2013;Reed II 2002). In line with studies from the field of psychology, numerous marketing studies have also adopted an interdisciplinary approach that considers the influence of various factors on the self-concept (for details see Appendix Table 1).…”
Section: The Self-concept and Consumptionmentioning
confidence: 99%
“…Consequently, consumer researchers should also use multiple theoretical lenses to explore consumer phenomena (Pham 2013) and adopt an interdisciplinary perspective to study the self-concept across its full life cycle (McConnell 2011). Adopting a wide variety of perspectives might potentially reveal new insights into how the selfconcept impacts brand attitude.…”
Section: Introductionmentioning
confidence: 99%
“…First, identity is multifaceted (Burke, 1980;Deaux, 1992). Thus, people define themselves with multiple identity aspects including traits, behaviors, roles, relationships, and group memberships (McConnell, 2010;Vignoles et al, 2006). Second, identity is malleable (Markus & Wurf, 1987).…”
Section: Studymentioning
confidence: 99%